PENGARUH SENAM KAKI DIABETIK TERHADAP PENURUNAN RISIKO ULKUS DIABETIKUM PADA PASIEN DIABETES MELLITUS TIPE 2 DI PUSKESMAS TAUPAH BARAT KECAMATAN TAUPAH BARAT KABUPATEN SIMEULE TAHUN 2020 - Yulis Hati; Dirayati Sharfina; Zamawawi (Jurnal Ilmiah Kebidanan Imelda, 2020)
Diabetes mellitus is a chronic disease that cannot be cured but can be controlled which can cause various complications. To reduce the risk of complications due to diabetes mellitus, diabetes exercise exercises can be done. This study aims to find out the Effect of Diabetic Foot Gymnastics on Reducing the Risk of Diabetic Ulcer in Type 2 Diabetes Mellitus Patients in West Taupah Health Center, West Taupah District, Simeule Regency 2020. This study uses a Pre-Experimental. The population in this study were all people with diabetes mellitus who visited the West Taupah Health Center as many as 32 people. The sampling technique used a purposive sampling technique of 20 people. The results showed that the risk of diabetic ulcers before the implementation of diabetes foot exercises at the West Taupah Health Center was mostly high risk. The risk of diabetic ulcers after the implementation of diabetes foot exercises at the West Taupah Health Center was mostly low risk. There is an Influence before and after the implementation of Diabetic Foot Gymnastics on the Reduction of the Risk of Diabetic Ulcer in Type 2 Diabetes Mellitus Patients in West Taupah Health Center, West Taupah Subdistrict, Simeule Regency in 2020 with p = 0.0001 <α = 0.05. Suggestions in this study, especially for health workers should continue to try to do diabetic foot exercises on a scheduled basis in order to minimize the risk of diabetic ulcers.